1999
DOI: 10.1287/moor.24.1.1
|View full text |Cite
|
Sign up to set email alerts
|

On a Representation of the Matching Polytope Via Semidefinite Liftings

Abstract: We consider the relaxation of the matching polytope defined by the non-negativity and degree constraints. We prove that given an undirected graph on n nodes and the corresponding relaxation of the matching polytope, n /2 iterations of the Lovász-Schrijver semidefinite lifting procedure are needed to obtain the matching polytope, in the worst case. We show that n /2 iterations of the procedure always suffice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 3 publications
2
28
0
Order By: Relevance
“…Stephen and Tunçel (1999) show that α(G) = n−1 2 iterations of the N + operator are needed for finding ST(G). Therefore, this gives an instance of a graph G for which ST(G) = Q α−1 (FR(G)) is strictly contained in N α−1 + (FR(G)).…”
Section: Application To the Stable Set Polytopementioning
confidence: 99%
“…Stephen and Tunçel (1999) show that α(G) = n−1 2 iterations of the N + operator are needed for finding ST(G). Therefore, this gives an instance of a graph G for which ST(G) = Q α−1 (FR(G)) is strictly contained in N α−1 + (FR(G)).…”
Section: Application To the Stable Set Polytopementioning
confidence: 99%
“…Theorem 1.3 For n = 2d + 1, the Sherali-Adams rank of the matching polytope, in the worst case over all n-vertex graphs, is 2d − 1. Theorem 1.3 answers for the Sherali-Adams hierarchy a question initially posed by Lovász and Schrijver about the rank of the matching polytope in the LS + hierarchy, which was answered by Stephen and Tunçel [27].…”
Section: Introductionmentioning
confidence: 96%
“…For n = 2d + 1, they showed that the rank lies between 2d and 2d 2 − 1 in the LS hierarchy, and is at most d in the LS + hierarchy. Stephen and Tunçel [27] subsequently proved that the LS + -rank is exactly d, and Goemans and Tunçel [15] improved the upper bound on LS-rank to d 2 . Aguilera, Bianchi and Nasini [1] show that the LS-rank is strictly larger than d, and also that the rank in the weaker Balas-Ceria-Cornuéjols hierarchy is exactly d 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Stephen and Tunçel [29] showed that n iterations are needed for finding the matching polytope of K 2n+1 (starting with the polytope defined by nonnegativity and the degree constraints) using the N + operator. Recently, Cook and Dash [8] and Goemans and Tunçel [12] constructed examples where positive semidefiniteness does not help; namely, the same number d of iterations is needed for finding some d-dimensional polytope P using the N or the N + operator.…”
Section: Introduction Lovász and Schrijvermentioning
confidence: 99%